DAMPAK PERKEMBANGAN KOTA TERHADAP LINGKUNGAN SOSIAL MASYARAKAT - Susatyo Adhi Pramono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2006)
AbstractÂ Development of town becomes fascination of people around to urbanization. The firm life of city and desire to live although without skill causes social problems in complex urban community.Â Keyword : city development, social environment problems